Effect of a quality improvement program on compliance to the sepsis bundle in non-ICU patients: a multicenter prospective before and after cohort study - Monti, Gianpaola; Rezoagli, Emanuele; Calini, Angelo; Nova, Alice; Marchesi, Silvia; Nattino, Giovanni; Carrara, Greta; Morra, Sergio; Cortellaro, Francesca; Savioli, Monica; Capra Marzani, Federico; Tresoldi, Moreno; et al. (Frontiers in Medicine, 2023)
Objective:Sepsis and septic shock are major challenge and economic burden to healthcare,impacting millions of people globally and representing significant causes of mortality.Recently,a large number of quality improvement programs focused on sepsis resuscitation bundles were instituted worldwide.These educative initiatives shown to be associated with improvements in clinical outcome.We aim to evaluate the impact of a multifaceted quality implementing program(QIP)on the compliance of a“simplified 1-hour bundle”(Sepsis-6)and hospital mortality of severe sepsis and septic shock patients out of Intensive Care Unit(ICU). Methods:Emergency Departments(EDs)and Medical Wards(MWs)of 12 Academic and Non-Academic Hospitals in Lombardy Region(Northern Italy)were involved in a multifaceted QIP,which included educational and organizational interventions.Patients with severe sepsis or septic shock according to Sepsis-2 criteria were enrolled in two periods:1)May 2011-November 2011(before-QIP cohort);2)August 2012-June 2013(after-QIP cohort). Measurements and main results:The effect of QIP on bundle compliance and hospital mortality was evaluated in a before-after analysis.We enrolled 467 patients in the before-QIPgroup and 656 in the after-QIPgroup.At enrollment,septic shock was diagnosed in 50% of patients,similarly between the two periods.In the after-QIP group,we observed an increased compliance to“simplified rapid (1hr) intervention bundle”(the Sepsis Six bundle-S6)at three time-points evaluated(1-hour,13.7to18.7%,p=0.018;3-hour,37.1to48.0%,p=0.013;overall study period,46.2to57.9%,p<0.001).We analyzed the compliance to S6 and hospital mortality in the before-and after-QIP period stratifying the two patients’ cohorts by admission characteristics.Adherence to S6 bundle was increased in patients with severe sepsis in the absence of shock,in patients with a serum lactate<4.0 mmol/L,and in patients with hypotension at the time of enrollment,regardless the type of admission(from EDs or MWs).Subsequently,in an observational analysis,we also investigated the relation between bundle compliance and hospital mortality by logistic regression.In the after-QIP cohort,we observed a lower in-hospital mortality than that observed in the before-QIP cohort.After adjustment for confounders,the QIP was independently associated with an improved in hospital mortality.Among the single S6 procedures applied within the first hour from sepsis diagnosis,compliance for blood culture and antibiotic therapy appeared significantly associated with a reduced in-hospital mortality. Conclusions:A multi-faceted QIP aimed at promoting an early simplified bundle of care for the management of septic patients out of ICU was associated with improved compliance to sepsis bundles and a lower in-hospital mortality.